2022
DOI: 10.1007/s44197-022-00031-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COVID-19 Fatality: A Worldwide Analysis of the Pandemic over Time and in Latin America

Abstract: SARS-CoV-2 has infected over one hundred million people worldwide and has affected Latin America particularly severely in terms of both cases and deaths. This study aims to determine the association between SARS-CoV-2 testing and COVID-19 fatality rate worldwide over 8 months and to examine how this relationship differs between Latin America and all other countries. This cross-sectional study used March 2021 data from 169 countries. Multivariate regressions predicted COVID-19 fatality (outcome) from the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…A systematic review and meta-analysis of the first year of the pandemic identified 46 studies in which it found a higher incidence of BSI in patients with COVID-19 than without it (OR 2.77; 95% CI 1.53-5.02), with an incidence of 29.6% of patients admitted to the ICU (95% CI, 21.7-31.8%) and with a mortality of 41% (95% CI, 30-52.8%), a range within which our data are found. The data also seem consistent with those observed in the first and second waves in Colombia, with mortality that seemed to be affected by the time at which patients were treated [ 15 ], similar to that observed in other Latin American countries [ 16 ].…”
Section: Discussionsupporting
confidence: 86%
“…A systematic review and meta-analysis of the first year of the pandemic identified 46 studies in which it found a higher incidence of BSI in patients with COVID-19 than without it (OR 2.77; 95% CI 1.53-5.02), with an incidence of 29.6% of patients admitted to the ICU (95% CI, 21.7-31.8%) and with a mortality of 41% (95% CI, 30-52.8%), a range within which our data are found. The data also seem consistent with those observed in the first and second waves in Colombia, with mortality that seemed to be affected by the time at which patients were treated [ 15 ], similar to that observed in other Latin American countries [ 16 ].…”
Section: Discussionsupporting
confidence: 86%
“…In October 2022, PAHO’s director reassured the region that disease trends insinuated a potential transition of the pandemic from an acute phase to a phase of sustained control [ 100 ]. Through 2022, the United States donated over 70 million COVID-19 vaccines to LAC directly and via the COVID-19 Vaccines Global Access (COVAX) partnership, with top recipients including Mexico (16.9 million doses), Guatemala (8.5 million doses), and Colombia (7 million doses) [ 100 , 131 , 132 ]. Larger agreements and agencies such as COVAX relied on a variety of vaccine types, mainly including messenger RNA (mRNA)–based vaccines (Pfizer-BioNTech, Moderna) and viral vector vaccines (Oxford University-AstraZeneca, Johnson & Johnson, Sputnik V) [ 133 - 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors have reported worldwide country-level COVID-19 mortality risk factors using data close to time of publication. Implicated risk factors include general pre-pandemic variables comprising country-level demographics (population ≥ 60 years 15 ); socioeconomic and governance factors e.g., higher GDP per capita 16 , 17 , higher income disparity 16 , higher transport infrastructure quality and lower government effectiveness 18 ; national healthcare metrics including lower general health expenditure, lower infectious disease system responsiveness and greater accountability 19 ; and population health characteristics like higher prevalence of obesity 15 , 16 , chronic obstructive pulmonary disease, Alzheimer’s disease, and depression 17 . Reported risk factors also comprise pandemic-specific variables.…”
Section: Introductionmentioning
confidence: 99%
“…Reported risk factors also comprise pandemic-specific variables. These include pandemic features e.g., duration 15 and case load 19 ; pandemic-associated public health policies inclusive of delayed international travel restrictions 15 and lower testing 18 ; and pandemic-associated public behaviours, e.g., shorter duration of mask wearing 15 . In addition, prior work also explored worldwide country-level COVID-19 mortality with a focus on select predictors, for example health system parameters 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%